Medical education in Bangladesh: Is there room for improvement? - Faiz, M Abul (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i2.3821 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):1-3